Les mots de trop - Les mots de trop (2021)
Les mots de trop est un outil de lutte et de sensibilisation à destination de tous·tes les étudiant·es des milieux de la culture.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; arts; belgique; capacitisme; discipline; france; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; suisse; système colonial; systèmes d'oppressions; thématiques; témoignages; violences

Metaepistemic Injustice and Intellectual Disability: a Pluralist Account of Epistemic Agency - Catala, Amandine (Ethical Theory and Moral Practice, 2020)
The literature on epistemic injustice currently displays a logocentric or propositional bias that excludes people with intellectual disabilities from the scope of epistemic agency and the demands of epistemic justice. This paper develops an account of epistemic agency and injustice that is inclusive of both people with and people without intellectual disabilities. I begin by specifying the hitherto undertheorized notion of epistemic agency. I develop a broader, pluralist account of epistemic agency, which relies on a conception of knowledge that accounts not only for propositional knowing, but also for other types of knowing that have been largely neglected in debates on epistemic injustice and agency. Based on this pluralist account of epistemic agency, I then show that people with intellectual disabilities qualify as epistemic agents and therefore as subjects of epistemic justice. Finally, I argue that this pluralist account of epistemic agency pushes us to revisit the current conception of epistemic injustice and to expand its taxonomy in two important ways.
Keywords: EDI; agentivité épistémique; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; handicap intellectuel; injustices épistémiques; inégalités; justice sociale; justice épistémique; philosophie; savoir propositionnel; sciences humaines; systèmes d'oppressions; taxonomie des savoirs; thématiques; violences; éthique

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Dirty river: A queer femme of color dreaming her way home - Piepzna-Samarasinha, Leah Lakshmi (Arsenal Pulp Press, 2015)
Finaliste du Prix littéraire Lambda et du Prix Judy Grahn pour la non-fiction lesbienne En 1996, la poète Leah Lakshmi Piepzna-Samarasinha, portant seulement deux sacs à dos, a pris un bus Greyhound en Amérique et s'est enfuie au Canada. Iel s'est retrouvé.e à Toronto, où iel a été accueilli.e par une communauté de punks queer de couleur offrant des promesses d'amour et de révolution, mais iel est resté.e hanté.e par les raisons pour lesquelles iel a quitté la maison en premier lieu. Ce mémoire passionné et captivant est un mélange de rêves et de cauchemars, de files d'attente devant les tribunaux de l'immigration et de soirées dansantes queer sud-asiatiques ; Il s'agit d'une feuille de route intensément personnelle et d'un récit tragi-comique intersectionnel qui révèle comment une femme queer handicapée de couleur et survivante d'abus navigue sur la rivière sale d'un passé pas si lointain et, comme le suggère le sous-titre, « rêve de rentrer chez elle ». "
Keywords: amériques; approches et analyses; canada; capacitisme; identités LGBTQIA2+; mémoire collective; queer; queer of color; racisme; récit de vie; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; états-unis

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

From Social Construction to Social Justice: Transforming How We Teach about Intersexuality - Koyama, Emi; Weasel, Lisa (Women's Studies Quarterly, 2002)
Keywords: LGBTQIA2+; approches et analyses; capacitisme; corps; cours; discipline; intersexuation; justice sociale; premier cycle; pédagogie; santé; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap